Metformin: the past, presence, and future - Alušík, Š; Paluch, Z (Minerva medica, 2015)
The authors trace the history of metformin and its clinical use to the present day. Recent insights into its mode of action and latest data from experimental and clinical medicine have unraveled novel properties of metformin, which may be particularly useful in the treatment of conditions other than diabetes. Results of ongoing clinical trials will show whether or not the hypoglycemic effect of metformin will become only one of the many to be employed in clinical practice.
Keywords: klinické zkoušky jako téma; Weight Loss; Evidence-Based Medicine; výsledek terapie; metformin; Risk Assessment; Diabetes Mellitus, Type 2; aplikace orální; diabetes mellitus 2. typu; hypoglykemika; Clinical Trials as Topic; hodnocení rizik; Randomized Controlled Trials as Topic; Humans; hmotnostní úbytek; medicína založená na důkazech; Administration, Oral; rizikové faktory; randomizované kontrolované studie jako téma; Risk Factors; Hypoglycemic Agents; Treatment Outcome; Metformin; lidé